Penanganan Surat Masuk Dengan Aplikasi Dropbox Untuk Efektifivitas Komunikasi Internal di Era Digital - Tengku Sitti Rochmah; Chandra Hendriyani; Shafira Ramadhanty (Jurnal Sekretaris dan Administrasi Bisnis, 2020)
The rapid development of technology in the digital era is driving changes in the way things work from manual to computerized. Changing the platform to computerization in administration is very helpful for companies, one of which is in cloud computing-based data storage through the use of the Dropbox application. The approved technology will provide benefits consisting of costs incurred, approved operational, and optimization of resources for the company. The purpose of this research is to study the process of implementing incoming mail and distributing mail using the Dropbox application and the benefits that come after distributing mail using the Dropdox application. The research method used is descriptive discussion. Data collection techniques carried out by observation, interviews with branch unit secretaries, and literature studies from books, journals, and documents relating to the discussion of research. The results of the study show that research and distribution of incoming mails using Dropbox conducted by BPJS Employment Cimahi in the digital era is currently facilitating work processes and internal communication between employees and encouraging new goals for companies that can be used quickly.